Material Effect on Entrepreneurship Learning towards Interest in Entrepreneurship Activities of Students - Yamin, Martinis; Aswirna, Prima; Asnawir; Fahmi, Reza; Nurdin, Syafruddin (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
This paper starts from the fact that, even though entrepreneurship learning materials (enterpreunorships) has been taught in the lecture material at IAIN Imam Bonjol Padang. But the number of students interested in entrepreneurship spirit is still limited. Further research using quantitative methods, with data analysis techniques are Linear regression analyzes were processed with SPSS version 20 .0 for windows. The independent variables in this study is a matter of entrepreneurship courses and the dependent variable interest in entrepreneurship. The population in this study students Propagation Department of Management Faculty of Da’wa and Communication Studies IAIN Imam Bonjol Padang Force 2013, which amounted to 52 people. Sampling research using techniques total sampling. Data collection techniques used in this Research has pe is a psychological scale, which is based on the Likert scale models, this study used two psychological scale. Based on the analysis of experimental data showed a simple linear regression with t> t table (2.967 ≥ 2.009) then hipot esis work (H a) is accepted, means that the material influences of entrepreneurship courses to student interest in entrepreneurship Propagation Department of Management Faculty of Da’wa and Communication Studies IAIN Imam Bonjol Padang.